The Juridical Implications of the Status of Children Out of Wedlock after the Stipulation of the Constitutional Court Decision Number: 46/PUUVIII/2010 - Paburru, Faely (Jurnal Konstatering, 2022)
This study aims to: 1. To find out the juridical implications of the position of illegitimate children after the stipulation of the Constitutional Court decision No: 46/PUUVIII/2010. 2. To find out the distribution of inheritance rights for children out of wedlock if there is a blood relationship with children out of wedlock. 3. Deed of inheritance rights issued by a notary. The approach in this research is the empirical juridical approach. Empirical juridical research is a problem approach regarding matters that are juridical in nature and the existing facts regarding matters that are juridical in nature. Empirical legal research or sociological research is legal research that uses primary data. The results of this study: 1. Juridical implications of the status of children outside of marriage after the stipulation of the Constitutional Court Decision Number: 46/PUUVIII/2010. The implications that arise from the presence of the Constitutional Court Decision Number 46/PUU-VIII/2010, children out of wedlock in Islamic law still only have the right to have family relations with their mother and family from their mother's side. As stated in Article 100 of the Compilation of Islamic Law (KHI) which reads: "Children born out of wedlock only have a family relationship with their mother and their mother's family". Therefore, if the adulteress is the father, then the male and female children of adultery do not have the right to inherit. However, if the deceased is the mother, then he has the right to be the heir. 2. Distribution of inheritance rights for children out of wedlock if there is blood relationship with children out of wedlock. Distribution of inheritance for children out of wedlock if it can be proven that there is a blood relationship between the child out of wedlock and his biological father, then the child out of wedlock can inherit together with the heirs of Group I. If the parents of the child out of wedlock pass away leaving legitimate offspring and/or the husband/wife who lives the longest, then the out of wedlock child he admits inherits one-third of what they were originally supposed to get if they were legitimate children (article 863 BW part one). 3. Deed of Inheritance Issued by a Notary. The deed of inheritance rights drawn up by a notary in the form of minutes of the power of attorney can be considered as perfect evidence. "Because the deed was made in accordance with the procedure for making an authentic deed according to the Law on Notary Position."Keywords: Children; Court; Marriage.